ISOLASI DNA METAGENOMIK DALAM RANGKA STUDI METANOGENESIS PADA TANAH SAWAH - Ni Luh Putu Mustika Praptiwi; Iryanti Eka Suprihatin; I Nengah Wirajana (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
Metagenomic is a new approach of complex genomes analysis from environmental samples. Isolation of total DNA from rice field soil sample has been conducted. Rice field, as an agriculture land, has been known to contribute 76% of total methane (CH4). The purpose of this study was to obtain metagenomic DNA isolated from rice field soil in order to study methanogenesis. Metagenomic DNA was isolated by direct and indirect cell lysis methods. Direct cell lysis method was conducted by directly lysing the cells in soil matrix followed by separation of DNA from the matrix and cell debris. Isolation of metagenomic DNA with indirect cell lysis method was carried out by cell separation from soil matrix followed by cell lysis. Metagenomic DNA were analyzed by agarose gel electrophoresis and UV-Vis spectrophotometry at ? 230, 260, and 280 nm. The results showed that metagenomic DNA could be isolated from rice field soil samples using direct and indirect cell lysis methods. Electrophoresis results showed that total DNA quality obtained by the indirect cell lysis was relatively less fragmented compared with direct cell lysis method. Spectrophotometric analysis showed that the total DNA isolated by indirect cell lysis was contaminated by humic acid more than metagenomic DNA isolated by direct cell lysis method. However, the metagenomic DNA by indirect cell lysis was contaminated by protein less than metagenomic DNA that obtained by direct cell lysis method.